The Relationship between Mindfulness and Self-Efficacy in Mahasantri Memorizing Qur’an with Peer Support being Moderating Variable - Badriyah, Nurul; Hapsari, Maharani Tyas Budi (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
This study aims to explore the relationship between mindfulness and self-efficacy moderated by peer support in al-Qur'an memorization mahasantri. This moderation research involved respondents of al-Qur'an memorization mahasantri with an age range of 18-24 years (N = 162) with sampling using probability sampling, namely random sampling. Data analysis using Jamovi. Based on hypothesis testing using the medmod test, the results show that there is a significant direct positive relationship between mindfulness and self-efficacy in Al-Qur'an memorization students with a z value = 2.31 (p = 0.021) but the interaction effect between mindfulness and peer support shows a negative and insignificant correlation with a z value = -1. 02 (p = 0.308) which means that peer support is not able to moderate the indirect relationship between mindfulness and self-efficacy. however, peer support as a moderating variable has a positive correlation with self-efficacy. students with high mindfulness will have high self-efficacy as well. The implication of this research is that the development of mindfulness and peer support in mahasantri needs to be considered in the management system of higher education and pesantren so that self-efficacy problems do not occur in mahasantri